STUDIES TENDING TO ESTABLISH INTEGRATED CONTROL OF PASTURE SALIVITES - JIMÉNEZ-G., JAIME A. (Revista Colombiana de Entomología, 1978)
Several experiments were conducted to study some aspects of the Spittlebug Aeneolamia varia, which causes severe damage to grasses, especially Brachiaria decumbens, in the Colombian Eastern Plains, where the post is known as "Salivita". According to the result, the main damage is done by the adults, which besides sucking the sap, inject toxic substances to the plant. It was observed that the eggs undergo diapause, which allows them to survive the dry season, and immediately the rainy season starts in March, the nymphs appear as a serious problem. The main biological control factor of the insect population is a disease caused by the fungus Metarrhizium anisopliae. Cultural methods, such as burning and disc-harrowing proved to provide the best control.